Modelling And Forecasting Of Flow Rate, Water Level And Water Quality Of Muda River And Beris Dam At Sungai Muda Catchment, Kedah Darul Aman, Malaysia - Hossain, Md. Azmal (2012)
This thesis reports whether seasonal variation has any impact on water quality of Sungai Muda catchment, the factors responsible of large variation in water quality in Sungai Muda catchment, the modeling and forecasting of monthly flow rate of Sungai Muda catchment, water elevation of Beris dam and feasibility study of another channel to retain water to alleviate flood and loading of main dam. Water quality data was collected from the year 2001 to 2004 from six sampling stations in Sungai Muda catchment. Monthly water flow of Jeniang of Sungai Muda from the year 1947 to 2001 and reservoir elevation data of Beris Dam from January 2006 to March 2009 were analyzed.